Respuesta :

cher
Equation 1)  4x = 3y - 2
Equation 2)  18 = 3x + y

Turn both equations into ax + by = c form.

Subtract 3y from both sides on equation 1, as well as subtracting 3x from both sides on the 2nd equation. Then, subtract 18 from both sides, and then subtract y from both sides, on the 2nd equation.

1)   4x - 3y= -2

2)  -3x - y = -18

Multiply ALL of equation 2 by 3.

2)  3(-3x - y = -18)

Simplify.

2)  -9x - 3y = -54
1)  4x - 3y = -2

Subtract equations from one another.

-13x = -52

Divide both sides by -13/

x = 4

Plug in 4 for x in the first equation.

4x - 3y = -2

4(4) - 3y = -2

Simplify.

16 - 3y = -2

Subtract 16 from both sides.

-3y = -18

Divide both sides by -3.

y = 6

So, x = 4, y = 6

A : (4, 6)

~Hope I helped!~